De novo Assembly and Characterization of the Fruit Transcriptome of Idesia polycarpa Reveals Candidate Genes for Lipid Biosynthesis - Li, Rong-Jun; Gao, Xiang; Li, Lin-Mao; Liu, Xiu-Lin; Wang, Zhou-Ya; Lü, Shi-you (Frontiers in Plant Science, 2016)
Idesia polycarpa, is a valuable oilseed-producing tree of the Flacourtiaceae family that has the potential to fulfill edible oil production and is also a possible biofuel feedstock. The fruit is unique in that it contains both saturated and unsaturated lipids present in pericarp and seed, respectively. However, triglyceride synthesis and storage in tissues outside of the seeds has been poorly studied in previous researches. To gain insight into the unique properties of I. polycarpa fruit lipid synthesis, biochemical, and transcriptomic approaches were used to compare the lipid accumulation between pericarp and seed of the fruit. Lipid accumulation rates, final lipid content and composition were significantly different between two tissues. Furthermore, we described the annotated transcriptome assembly and differential gene expression analysis generated from the pericarp and seed tissues. The data allowed the identification of distinct candidate genes and reconstruction of lipid pathways, which may explain the differences of oil synthesis between the two tissues. The results may be useful for engineering alternative pathways for lipid production in non-seed or vegetative tissues.